Communicating Gender Equality: Critical Analysis of Gendered Language in Social Science Textbooks for Alpha Generation - Purnomo, Agustina Multi; Fauziah, R. Siti Pupu; Martin, Abraham Yazdi; Roestamy, Martin; Nita, Kamala Sia Rio; Warizal, Warizal (International Journal of Language Education, 2025)
The study examined how textbooks, as a communication tool, shape gender-related messages and gender equality in social learning by analyzing gendered language in 9th-grade social science textbooks used by Indonesia's first Alpha Generation. The study adopted a sociological perspective to analyze the content and structure of the ninth-grade Merdeka curriculum textbook as an ideological medium of communication. It employed a mixed-methods approach, combining critical content analysis of textual and visual elements with a student survey involving 389 respondents. The findings revealed that the textbook conveyed gender bias through its text and figures, even though Indonesian permits grammatical neutrality. The survey showed that 9th-grade students perceived gender inequality, as they mentioned male figures far more frequently in visuals (277 vs. 67; bias ratio 4.13) and texts (233 vs. 111; bias ratio 2.10), indicating that they actively interpreted male dominance in the textbook's content. The results confirmed that textbooks shaped gendered inequality through implicit communication. The Alpha generation, shaped by constant exposure to digital narratives, may internalize patterns that hinder equitable educational goals. This study suggested that textbooks express social values and educators should create books that offer inclusive perspectives on gender roles to promote gender equality in education.